Bioactivity Screening of Endophytic Fungus Eutypa linearis isolated from Coleus amboinicus (Lour.) - Baiq Maylinda Gemantari; Fitra Romadhonsyah; Arief Nurrochmad; Subagus Wahyuono; Puji Astuti (Universitas Gadjah Mada, 2021)
Coleus amboinicus (Lour.) is a medicinal plant containing various bioactive compounds. Endophytes are microorganisms living inside intracellular tissue of plants and known as the source of bioactive compounds. In order to explore the potential of endophyte in producing novel bioactive compounds, this study focused on isolating endophytic fungi from the leaves of C.amboinicus, characterisation and screening their metabolite bioactivity during submerged culture fermentation. Isolation of endophytic fungi from the leaves segment of C.amboinicus was conducted on PDA media and fungus identification was carried out by analyzing its morphology and molecular examination. The production of metabolites was examined using thin layer chromatography and gas chromatography. Identification of the endophytic fungus showed 98.84% similarity with Eutypa linearis. This species was fermented submergedly in PDB medium for 14 days under dark and exposed to light and the fermentation broth was extracted using ethyl acetate. The results showed that exposure to the light did not significantly influence metabolite production. The ethyl acetate extract exhibited antioxidant and cytotoxic activities. Antioxidant activity of this extract as examined by DPPH assay showed IC50 of 105.31 ± 2.11 µg/mL. Cytotoxic activity against Hela cell line was known to be the best among other cell lines (IC50 301.53 ± 11.34 µg/mL) although it was found to be non selective (SI<1). The extract contained five major compounds namely Benzenemethanol, 4-nitro-(CAS) p-Nitrobenzyl alcohol; 2-Pentadecanone (CAS) Pentadecan-2-one; (1R*,6S*,10R*)-5,5-Dimethyl-11,12-dioxatricyclo[8.2.1.0(1,6)] tridecan-10-ol; 9,12-Octadecadienoic acid (Z,Z)-, methyl ester (CAS) Methyl linoleate; and 3-Furanacetic acid, 4-hexyl-2,5-dihydro-2,5-dioxo- (CAS) 2-carboxymethyl-3-N-hexyl-maleic anhydride.